Exploring the Molecular Composition of Dissolved Organic Matter and Its Connection to Microbial Communities in Industrial-Scale Anaerobic Digestion of Chicken Manure - Juan Hu; Yurui Zeng; Aibin Hu; Xiaofeng Wang (Toxics)
Anaerobic digestion (AD) technology offers significant advantages in addressing environmental issues arising from the intensification of livestock production since it enables waste reduction and energy recovery. However, the molecular composition of dissolved organic matter (DOM) and its linkages to microbial biodiversity during the industrial-scale AD process of chicken manure (CM) remains unclear. In this study, the chemical structure of CM digestate-derived DOM was characterized by using multi-spectroscopic techniques and ultrahigh-resolution mass spectrometry, and the microbial composition was detected by using 16S rRNA gene sequencing. The results revealed that the DOM contained abundant free amino acids and protein-like compounds but fewer humic-like substances, identified as lignin/carboxylate-rich alicyclic molecules, lipids, and proteins/aliphatic compounds featuring enriched S5–6O1 and N1–5OX fragments. In addition, the 16S rRNA results revealed microorganisms that were centered on metabolic function in the production of volatile fatty acids, H2S/CH4, and the hydrolysis reaction in the AD process. Free amino acids and protein-like compounds were mainly associated with hydrolysis reactions and H2S production functional microorganisms. Lignin/carboxylate-rich alicyclic molecules were linked to microorganisms possessing hydrolysis reactions and, indirectly, CH4 production. This study elucidates the linkage with the microbial and molecular composition of DOM, establishing a theoretical foundation for employing AD in the disposal of CM.